2018
DOI: 10.1186/s13045-017-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GD2/4-1BB chimeric antigen receptor T cell therapy for the treatment of Chinese melanoma patients

Abstract: BackgroundChimeric antigen receptor (CAR)-engineered T cells have demonstrated promising clinical efficacy in patients with B cell lymphoma. However, the application of CAR-T cell therapy in the treatment of other solid tumors has been limited. We incorporated 4-1BB into the anti-GD2 CAR-T cells to test their cytotoxicity in melanoma in vitro and in vivo. Moreover, we reported the expression of ganglioside GD2 in non-Caucasian melanoma populations for the first time, thus providing a basis for future clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(157 citation statements)
references
References 52 publications
3
152
2
Order By: Relevance
“…injection, i.v. injection of M28z cells showed less robust function in controlling tumor growth, as observed in previous studies (33). M28z-TKO cells delivered through i.v.…”
Section: Tgf-β1 Negatively Regulates Car T Cell Cytotoxic Function VIsupporting
confidence: 72%
“…injection, i.v. injection of M28z cells showed less robust function in controlling tumor growth, as observed in previous studies (33). M28z-TKO cells delivered through i.v.…”
Section: Tgf-β1 Negatively Regulates Car T Cell Cytotoxic Function VIsupporting
confidence: 72%
“…For Caucasians, superficial diffuse melanoma is the most frequent melanoma and accounts for ~90% of all malignant melanoma cases. For persons of Asian and African descent, freckle-like melanoma accounts for 50-70% of all patients with malignant melanoma (9,10). In addition, malignant melanoma may be inherited, and it has been suggested that 10% of patients with melanoma have a family history (11).…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used targets for CAR-T therapy are surface antigens, such as carcinoembryonic antigen (CEA) for colorectal adenocarcinoma 175,176 , fibroblast activation protein for malignant pleural mesothelioma 177 , diganglioside GD2 for neuroblastoma 178 , glioblastoma 179 , melanoma 180 , and osteosarcoma 181 , human epidermal growth factor receptor 2 (HER2) for HER2-positive sarcoma 182 , mesothelin for pancreatic cancer 183 , IL-13 receptor α (IL-13Rα) for glioma 184 , and mutant αvβ6 integrin for pancreatic tumors 185 . TCR-engineered T cells always target the p-HLA complex.…”
Section: Use Of Genetically Engineered T Cells For Treating Solid Tumorsmentioning
confidence: 99%
“…First-generation CAR-T cells, which contain a CAR construct with only CD3ζ in the intracellular domain, showed limited antitumor efficacy in clinical trials 16,256 , mainly due to the lack of costimulatory molecules that are essential for T cell responses to antigens 257,258 . In fact, the intracellular signal transduction domain always includes the indispensable CD3ζ chain, which contains immunoreceptor tyrosine-based activation motifs (ITAMs) that function in signal transduction 259 , and one or more intracellular costimulatory molecules, such as CD28, 4-1BB (CD137), or CD27, to transmit activation signals 180,[260][261][262][263][264][265][266][267][268][269][270] . In terms of the intracellular signal domain, CARs have evolved from the first to the fourth generation.…”
Section: Intracellular Domainmentioning
confidence: 99%